Beyond assignment deadlines: Explaining academic stress through deadline behavior among university students - Susi Juniarti Pardosi; Darwis Robinson Manalu (Eduvista: Journal of Education and Innovation, 2026)
Deadline behavior, defined as the habit of completing academic assignments close to submission deadlines, is presumed to contribute to higher levels of academic stress among university students; however, empirical evidence specifically examining this relationship remains limited. This study aimed to analyze the effect of deadline behavior on academic stress among students at Universitas Methodist Indonesia. A quantitative associative design was employed involving 100 undergraduate students who completed a five-point Likert-scale questionnaire. The data were analyzed using simple linear regression with IBM SPSS Statistics 22. The findings revealed that deadline behavior had a positive and significant effect on academic stress (B = 0.278; t = 4.082; p < 0.001). The coefficient of determination (R² = 0.145) indicates that deadline behavior explained 14.5% of the variance in academic stress, while the remaining variance was influenced by factors outside the proposed model. These findings highlight the importance of effective time management as a preventive strategy for reducing academic stress and contribute to the growing literature on academic behavior in higher education. Abstrak Kebiasaan mengerjakan tugas mendekati batas waktu (deadline behavior) diduga menjadi salah satu penyebab meningkatnya stres akademik mahasiswa, namun penelitian yang secara khusus menguji pengaruh perilaku tersebut terhadap tingkat stres masih relatif terbatas. Penelitian ini bertujuan menganalisis pengaruh deadline behavior terhadap tingkat stres mahasiswa di Universitas Methodist Indonesia. Penelitian menggunakan pendekatan kuantitatif dengan desain asosiatif yang melibatkan 100 mahasiswa melalui penyebaran kuesioner skala Likert lima poin. Data dianalisis menggunakan regresi linear sederhana dengan bantuan IBM SPSS Statistics 22. Hasil penelitian menunjukkan bahwa deadline behavior berpengaruh positif dan signifikan terhadap tingkat stres akademik (B = 0,278; t = 4,082; p < 0,001). Nilai koefisien determinasi (R² = 0,145) menunjukkan bahwa deadline behavior menjelaskan 14,5% variasi tingkat stres akademik, sedangkan sisanya dipengaruhi oleh faktor lain di luar model penelitian. Temuan ini menegaskan pentingnya pengelolaan waktu sebagai strategi preventif dalam menekan stres akademik mahasiswa sekaligus memperkaya kajian mengenai perilaku akademik di pendidikan tinggi.